Localized Sound‐Integrated Display Speaker Using Crosstalk‐Free Piezoelectric Vibration Array - Inpyo Hong; Su Seok Choi (Advanced Science, 2025)
Abstract Beyond visual quality, features like sound and tactile feedback have become essential to enhancing user experience, resulting in more immersive, realistic displays. Multisensory displays engaging multiple senses are increasingly in demand. Panel‐integrated piezoelectric speakers represent a major advancement in audio‐visual technology, merging sound generation with display panels to enable compact, versatile designs in thin, flexible formats. However, challenges like sound crosstalk between exciters and non‐uniform frequency responses often compromise audio quality. To address these issues, frame‐based sound vibration isolation strategies are explored to localize surface vibrations and reduce interference across multiple exciters. Through experimental measurements and Finite Element Method (FEM) simulations, it is found that increasing frame height and width, along with using materials with different acoustic impedance for the diaphragm, significantly improved frequency response uniformity and reduced Total Harmonic Distortion (THD). These enhancements simplify speaker response compensation, ensuring reliable, high‐quality sound output. As demonstrated on a practical 13‐inch OLED display, these results confirm that vibration‐isolated, localized sound in multi‐array exciters overcomes prior limitations, advancing the acoustic performance of piezoelectric panel speakers. This study provides valuable insights for future developments in thin, flexible, display‐integrated audio systems, offering new possibilities in immersive, multisensory user experiences.